The use of Malay version of hearing handicap questionnaire on adults with hearing impairment : case study - Muhammad Shahanizam, Shamsuddin (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
The measurement of hearing handicap is important as it leads to better management of individual with hearing impairment. This research was conducted to study the hearing handicaps of adults with hearing impairment in relation to the degree, type and duration of hearing loss, by means of a simple questionnaire in Malay version. Ten unaided subjects participated in this study. All of them were above ·18 years of age, had hearing impairment and in good mental health. They were also willing to participate, able to answer and give comments on the questionnaire. The study was conducted at Audiology Clinic, Hospital of Universiti Sains Malaysia (HUSM), Kota Bharu, Kelantan. This research can be divided into two phases: the validation of questionnaire phase and the actual data collection phase. In the first phase, the hearing handicap questionnaire was constructed accordingly and then validated via a pilot study. During the actual data collection phase, participants were interviewed personally to flU in the questionnaire. In the questionnaire, ten most common listening conditions were constructed (based on thorough interviews and opinions from experts) and rating of 1-5 was used (I and 5 scale represents 'no problem' and 'severe difficulty', respectively). Audiogram of each participant was obtained, prior to the interview. Based on the audiogram, the participants were assigned into three groups: unilateral hearing loss, bilateral symmetrical hearing loss and bilateral asymmetrical groups. The result showed that the listening difficulties ranged from I 0% (I out of I 0 questions) to 20% (2 out of 10 questions) in the unilateral hearing loss group. For bilateral symmetrical hearing loss group, the range of difficulties was from 80% (8 out of 10 questions) to 100% (10 out of 10 questions). All subjects in bilateral asymmetrical hearing loss group reported 100% hearing difficulties (10 out of 10 questions). These findings are in agreement with previous studies and support the claimed relation between the degree of hearing loss and hearing handicap. This study also found that subjects with 'identical' hearing loss showed different degree of hearing handicap (i.e. the hearing handicap is unique). This suggests a management strategy to be 'specific' for each person with hearing loss. This study demonstrates some values of having a Malay version of hearing handicap questionnaire to measure the listening difficulties among hearing-impaired individuals. However, further studies (with bigger sample size) are required to determine the usefulness of this hearing handicap questionnaire, especially for clinical use.